2016
DOI: 10.1016/j.jtho.2016.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Ceritinib and Crizotinib as Initial ALK –Targeted Therapies in Previously Treated Advanced NSCLC: An Adjusted Comparison with External Controls

Abstract: In an adjusted comparison across separate clinical trials, ceritinib was associated with prolonged OS and PFS compared with crizotinib when used as initial ALK-targeted therapy for previously treated ALK-positive NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
(37 reference statements)
0
35
0
Order By: Relevance
“…In the absence of a randomized head to head study comparing the efficacy between ceritinib and crizotinib in the first‐line setting, previous studies addressed this by taking advantage of an indirect comparative approach using the patient cohort propensity score‐matched from the ASCEND 4 and PROFILE 1014 trials . In this indirect comparison, ceritinib showed a significantly better treatment efficacy than crizotinib . Although this approach provided preliminary and insightful findings, it remained limited by the unadjustable bias inherent in each trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of a randomized head to head study comparing the efficacy between ceritinib and crizotinib in the first‐line setting, previous studies addressed this by taking advantage of an indirect comparative approach using the patient cohort propensity score‐matched from the ASCEND 4 and PROFILE 1014 trials . In this indirect comparison, ceritinib showed a significantly better treatment efficacy than crizotinib . Although this approach provided preliminary and insightful findings, it remained limited by the unadjustable bias inherent in each trial.…”
Section: Discussionmentioning
confidence: 99%
“…4,14 In this indirect comparison, ceritinib showed a significantly better treatment efficacy than crizotinib. 19,20 Although this approach provided preliminary and insightful findings, it remained limited by the unadjustable bias inherent in each trial. The present study, otherwise analyzed in a manner of direct comparison, confirmed the finding noted in the previous indirect comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8.3 months, respectively, and 82.6 vs . 66.0% patient survival at 12 months, respectively) . Most recently, early data from the Phase III ASCEND‐5 study of 231 European patients showed that ALK‐positive NSCLC patients that progressed on crizotinib had a longer progression‐free survival with ceritinib than pemetrexed‐docetaxel (5.4 vs .…”
Section: Clinical Trials Investigating Alternatives To Crizotinib In mentioning
confidence: 99%
“…Only when patients were matched, median PFS and overall survival were longer in the ceritinib group in comparison to the crizotinib Group (13.8 vs. 8.3 months, respectively, and 82.6 vs. 66.0% patient survival at 12 months, respectively). 80 Most recently, early data from the Phase III ASCEND-5 study of 231 European patients showed that ALK-positive NSCLC patients that progressed on crizotinib had a longer progression-free survival with ceritinib than pemetrexed-docetaxel (5.4 vs. 1.6 months, respectively; p < 0.001), suggesting that second-line therapy should be with ceritinib and not chemotherapy. 81 As a result, ceritinib has conditional approval in Europe.…”
Section: Ceritinibmentioning
confidence: 99%